The domain swapping of human cystatin C induced by synchrotron radiation - Taube, Michal (Sci Rep, 2019)
Domain swapping is observed for many proteins with flexible conformations. This phenomenon is often associated with the development of conformational diseases. Importantly, domain swapping has been observed for human cystatin C (HCC), a protein capable of forming amyloid deposits in brain arteries. In this study, the ability of short exposure to high-intensity X-ray radiation to induce domain swapping in solutions of several HCC variants (wild-type HCC and V57G, V57D, V57N, V57P, and L68V mutants) was determined. The study was conducted using time-resolved small-angle X-ray scattering (TR-SAXS) synchrotron radiation. The protein samples were also analysed using small-angle neutron scattering and NMR diffusometry. Exposing HCC to synchrotron radiation (over 50 ms) led to a gradual increase in the dimeric fraction, and for exposures longer than 150 ms, the oligomer fraction was dominant. In contrast, the non-irradiated protein solutions, apart from the V57P variant, were predominantly monomeric (e.g., V57G) or in monomer/dimer equilibrium. This work might represent the first observation of domain swapping induced by high-intensity X-rays.